2007
DOI: 10.1016/j.cellsig.2007.07.021
|View full text |Cite
|
Sign up to set email alerts
|

ROCK I-mediated activation of NF-κB by RhoB

Abstract: RhoB is a short-lived protein whose expression is increased by a variety of extra-cellular stimuli including UV irradiation, epidermal growth factor (EGF) and transforming growth factor β (TGF-β). Whereas most Rho proteins are modified by the covalent attachment of a geranylgeranyl group, RhoB is unique in that it can exist in either a geranylgeranylated (RhoB-GG) or a farnesylated (RhoB-F) form. Although each form is proposed to have different cellular functions, the signaling events that underlie these diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 49 publications
(86 reference statements)
1
44
0
1
Order By: Relevance
“…Our data and that of other researchers have noted that ROCK inhibitors cause the cytokine secretion suppression of TNF-a, IL-6, and IL-1b from human macrophages, PBMCs, and synoviocytes (Doe et al, 2007;Rodriguez et al, 2007;He et al, 2008). The suppression of cytokine secretion by ROCK inhibitors in endothelial cells, leukocytes, and synoviocytes is attributed to the suppression of ROCK-mediated inactivation of IKKb and inhibition of phosphorylation of the RelA/p65 domain and by induction of IkBa phosphorylation, which leads to its degradation (Anwar et al, 2004;Rodriguez et al, 2007;He et al, 2008). As we improved the activity of ROCK, the suppressive activity against cytokine secretion of TNF-a, IL-1b, IL-6, IFN-g, IL-4, and IL-13 did not proportionally increase (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Our data and that of other researchers have noted that ROCK inhibitors cause the cytokine secretion suppression of TNF-a, IL-6, and IL-1b from human macrophages, PBMCs, and synoviocytes (Doe et al, 2007;Rodriguez et al, 2007;He et al, 2008). The suppression of cytokine secretion by ROCK inhibitors in endothelial cells, leukocytes, and synoviocytes is attributed to the suppression of ROCK-mediated inactivation of IKKb and inhibition of phosphorylation of the RelA/p65 domain and by induction of IkBa phosphorylation, which leads to its degradation (Anwar et al, 2004;Rodriguez et al, 2007;He et al, 2008). As we improved the activity of ROCK, the suppressive activity against cytokine secretion of TNF-a, IL-1b, IL-6, IFN-g, IL-4, and IL-13 did not proportionally increase (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…RhoB has been shown to localize to endocytic vesicles (Adamson et al, 1992), where it signals after activation by Vav2 (Gample and Mellor, 2002) through PRK1 to regulate the intracellular epithelial growth factor (EGF) trafficking to the lysosome (Gampel et al, 1999). In addition, RhoB activates NFkB, independently from PRK1, in a ROCK-I dependent fashion (Rodriguez et al, 2007). Moreover, RhoB is involved in the uPA/uPAR-dependent migration and invasion of prostate cancer cells.…”
Section: Rac Rho and Cdc42 In Two Dimensionsmentioning
confidence: 97%
“…Early work on RhoB reported that it localizes to endocytic vesicles 21 where, upon activation by Vav2, 22 it signals through PRK1 to regulate the kinetics of intracellular EGF trafficking to the lysosome 23 . Interestingly, work from Rodriguez et al revealed that RhoB activates NFκB, independently from PRK1, in a ROCK-I dependent manner 24 . More recent work from Ridley’s group has shown that the GTPase RhoB plays a key role in the uPA/uPAR-mediated migration and invasion of prostate cancer cells.…”
Section: Interplay Between Rho-family Gtpases During Cell Migrationmentioning
confidence: 99%